RETRACTED: Socio-economic effectiveness of children with autism spectrum disorders rehabilitation - Oshkordina Alla; Goncharova Nadezhda; Borzunov Igor; Khaitova Alexandrina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001